Edit Blindness: The relationship between attention and global change blindness in dynamic scenes. - Tim J. Smith; John M. Henderson (Bern Open Publishing, 2008)
Although we experience the visual world as a continuous, richly detailed space we often fail to notice large and significant changes. Such change blindness has been demonstrated for local object changes and changes to the visual form of whole images, however it is assumed that total changes from one image to another would be easily detected. Film editing presents such total changes several times a minute yet we rarely seem to be aware of them, a phenomenon we refer to here as edit blindness. This phenomenon has never been empirically demonstrated even though film editors believe they have at their disposal techniques that induce edit blindness, the Continuity Editing Rules. In the present study we tested the relationship between Continuity Editing Rules and edit blindness by instructing participants to detect edits while watching excerpts from feature films. Eye movements were recorded during the task. The results indicate that edits constructed according to the Continuity Editing Rules result in greater edit blindness than edits not adhering to the rules. A quarter of edits joining two viewpoints of the same scene were undetected and this increased to a third when the edit coincided with a sudden onset of motion. Some cuts may be missed due to suppression of the cut transients by coinciding with eyeblinks or saccadic eye movements but the majority seem to be due to inattentional blindness as viewers attend to the depicted narrative. In conclusion, this study presents the first empirical evidence of edit blindness and its relationship to natural attentional behaviour during dynamic scene viewing.